1994
DOI: 10.1001/jama.1994.03520160051042
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Gender Bias in Anatomy and Physical Diagnosis Text Illustrations

Abstract: In anatomy and physical diagnosis texts, women are underrepresented in illustrations of nonreproductive anatomy. The finding that males are depicted in a majority of nonreproductive anatomy illustrations may perpetuate the image of the male body as the normal or standard model for medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 17 publications
6
28
1
Order By: Relevance
“…These findings are in line with earlier studies on gender bias in textbooks 12–14 . Our content analysis is restricted to coverage, integration and accessibility.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in line with earlier studies on gender bias in textbooks 12–14 . Our content analysis is restricted to coverage, integration and accessibility.…”
Section: Discussionsupporting
confidence: 91%
“…Curricular bias, for instance, encompasses situations where the curriculum includes no coverage of gender‐related issues at all (invisibility), is guilty of stereotyping, or omits different perspectives (imbalance and selectivity). A study of anatomy textbooks published in 1994 reported a sex and gender bias where women were under‐represented in non‐reproductive anatomy 13 . In 1998 in Sweden, the screening of medical textbooks pertaining to four fields of practice, including public health, revealed gender bias on biomedical as well as psychosocial aspects 14 .…”
Section: Introductionmentioning
confidence: 99%
“…We concluded that, in terms of both imagery and text, many textbooks lack neutrality. This finding supports previous reports by Lawrence and Bendixen (), Mendelsohn et al (), and Giacomini et al (). In addition, we found that while there were some differences in attitudes between the medical students at Cardiff and Paris, overall while students recognized the importance of gender issues and did not wish to associate with sexism, most were unaware of the possible negative aspects of sexism within anatomy.…”
Section: Introductionsupporting
confidence: 94%
“…With respect to our hypothesis that “professional anatomists are more aware of the lack of gender neutrality within anatomical textbooks and for descriptions of sexual organs,” few recognized gender bias in the depiction of anatomy within textbooks, despite there being ample evidence from previous studies that contemporary textbooks of gross anatomy and surface anatomy most often lack gender neutrality. (Lawrence and Bendixen, ; Mendelsohn et al, ; Giacomini et al, ; Morgan et al, ). Lawrence and Bendixen () in particular emphasize the importance of this issue, when they suggest that anatomy has a key role in producing a “powerful and authoritative science of the human structure that is vital to advanced work in various areas of medical research and medical practice.” Their survey of 31 texts published in the United States of America found that contemporary textbooks of anatomy “perpetuate the conventions setting the male as the central model of anatomy” that helps to “maintain an anatomical hierarchy: male, then female; male as norm, female as different.” They concluded that Western culture is far from “creating from a nongendered human anatomy, one from which both male and female emerge as equally significant and intriguing variations.”…”
Section: Discussionmentioning
confidence: 99%
“…1 The authors looked at 4000 illustrations in 12 commonly used anatomy and diagnostic texts and found women "grossly under-represented in examples of non-reproductive anatomy." 1 Another important example comes from the New England Journal of Medicine.…”
Section: Preclinical Trainingmentioning
confidence: 99%